O83 Phase 1 study of an anti-CD27 agonist as monotherapy and in combination with pembrolizumab in patients with advanced solid tumors. (15th April 2020) - Shapira-Frommer, Ronnie; Dongen, Marloes GJ van; Dobrenkov, Konstantin; Chartash, Elliot; Liu, Fang; Li, Claire; Wnek, Richard; Patel, Manish
Abstract : Background: MK-5890 is a humanized agonist monoclonal antibody that binds to CD27 to provide a costimulatory signal that enhances T-cell–mediated responses. This first-in-human phase 1 study of MK-5890 evaluated the safety and efficacy of escalating doses of MK-5890 as monotherapy and in combination with pembrolizumab in patients with advanced solid tumors. Methods: Key eligibility criteria included histologically or cytologically confirmed advanced solid tumor, measurable disease by RECIST v1.1, and ECOG PS ≤1. MK-5890 was tested alone (dose range, 2-700 mg) or with pembrolizumab (fixed dose, 200 mg). Patients with disease progression following MK-5890 monotherapy were eligible to cross over to combination treatment. The primary objective was safety and tolerability. Objective response rate by investigator per RECIST v1.1 was also evaluated. The database cutoff for this analysis was May 30, 2019. Results: Of 44 patients enrolled, 25 received MK-5890 and 19 received MK-5890 plus pembrolizumab; their median age was 59.0 years, 61.4% were female, 47.7% had ECOG PS 1, and 13.6% previously received immune checkpoint inhibitor therapy. In the initial phase, dose-limiting toxicities (DLTs) were reported in 3 patients receiving MK-5890 and 1 patient receiving MK-5890 plus pembrolizumab; all DLTs were associated with infusion-related adverse events. Maximum tolerated dose was defined. Treatment-related adverse events (TRAEs) were reported in 40 patients (90.9%): 22 patients (88.0%) receiving MK-5890 and 18 patients (94.7%) receiving MK-5890 plus pembrolizumab. The most common TRAEs were fatigue (28.0%) and infusion-related reactions (28.0%) with MK-5890 and fatigue (36.8%) and pruritus (31.6%) with MK-5809 plus pembrolizumab. Grade 3-4 TRAEs were reported in 10 patients (22.7%): 6 patients (24.0%) receiving MK-5890 and 4 patients (21.1%) receiving MK-5890 plus pembrolizumab; no grade 5 events were observed. One patient (4.0%) achieved a partial response (PR) with MK-5890 and 1 patient (5.3%) achieved a PR with MK-5890 plus pembrolizumab. Fourteen patients entered the crossover phase to receive MK-5890 plus pembrolizumab. In the crossover phase, no DLTs were reported. TRAEs were reported in 12 patients (85.7%); the most common were pruritus (21.4%), rash (21.4%), and headache (14.3%). One patient (7.1%) reported grade 3-4 TRAEs of increased amylase and increased lipase; no grade 5 events were observed. Two patients (14.3%) achieved a complete response and 2 patients (14.3%) achieved a PR. Conclusions: Treatment with MK-5890, alone and in combination with pembrolizumab, demonstrated an acceptable safety profile. Early antitumor activity was observed in patients with advanced solid tumors in both monotherapy and combination therapy arms.